Tumor cell surface heparan sulfate as cryptic promoters or inhibitors of tumor growth and metastasis - Liu, Dongfang (The National Academy of Sciences, 2002)
Heparan sulfate glycosaminoglycans, present at the cell surface and in the extracellular matrix that surrounds cells, are important mediators of complex biological processes. Furthermore, it is now apparent that cells dynamically regulate the structure of their heparan sulfate “coat” to differentially regulate extracellular signals. In the present study, the importance of sequence information contained within tumor cell-surface heparan sulfate was investigated. Herein, we demonstrate that the heparan sulfate glycosaminoglycan coat present on tumor cells contains bioactive sequences that impinge on tumor-cell growth and metastasis. Importantly, we find that growth promoting as well as growth inhibiting sequences are contained within the polysaccharide coat. Furthermore, we find that the dynamic balance between these distinct polysaccharide populations regulates specific intracellular signal-transduction pathways. This study not only provides a framework for the development of polysaccharide-based anti-cancer molecules but also underscores the importance of understanding a cell's polysaccharide array in addition to its protein complement, to understand how genotype translates to phenotype in this postgenomic age.